Calibration of orifice plates with special emphasis on edge sharpness and eccentricity - Lebi, Juliu (Department of Mechanical Engineering, 2023)
A general review of the literature pertaining to flov1 measurement with orifice plates is presented. Special emphasis is laid on the factors influencing the coefficient of discharge Of orifice plates and. on the difference between the various engineering standards. Particular consideration is given to the effect on the discharge coefficient of rounding the upstream edge of the orifice plate and of changes in plate eccentricity. Various methods to calibrate orifice plates and to measure the edge roundness of orifice plates are discussed. Orifice plates with area ratios ranging from 0,1.to 0,55 were tested in order to evaluate variations in the coefficient of discharge with changes in: a) the upstream edge radius; b) the plate concentricity ty. The calibration tests were conducted with apparatus based on a system of weighing the working fluid which accumulates in a tank over an accurately determined time interval. In order to measure the upstream edge radius of an orifice plate, a lead foil holder was designed. Using the holder, accurate imprints of the edge profile were obtained in the lead foil. The apparatus used and the method of calibration is described in detail. Attention is drawn to the precautions required for accurate calibration. The method of calibration used was complicated by fluctuations in the differential pressure. It was found that the mean of twelve random pressure differential readings at a specific flow rate: did not vary by more than .f ·- o, 05 mm of mercury. Increasing the number of pressures